Structuralism and individualism in economic analysis : the "contractionary devaluation debate" in development economics - Charusheela, S., 1964- (New political economy (New York, N.Y.), 2005)
This book argues that the debates about the appropriate economic policies to follow in the developing world within the field of development economics are at heart debates about the appropriate ontology to ascribe to agents within the developing world.